Factors influencing employee motivation among public sector employees: a case of Kota Tinggi District Council (MDKT) / Siti Rashidah Rapiee - Rapiee, Siti Rashidah (Faculty of Business and Management, 2018)
Employee motivation is the very crucial parts in every organization in order to make their employee keep motivate in every task they were assigned. Most of the organization today realized that, it is important of having motivated employees to make them perform better in their task and have a positive thinking. It involved employee’s feeling about their work especially employees who experience challenging work. This paper investigates some of the factors that will influence employee motivation among public sector employees. Public sector employees may deal with creative and professional skills of work and they normally feel stress about their work. This study used main data collection method by using questionnaire and distribute to all employees at Kota Tinggi District Council (MDKT) that consist of eight departments. The total population is 180 employees and from the total population, the sample size of 123 respondents was drawn by using survey research. The finding of this study for independent variable which are “Organizational Culture” and “Working Environment” has support the hypothesis and significantly related to the employee motivation. For further study, the researcher suggested to add more factors and places where study is conducted.